Alternative framework and human resources for agricultural training and development in the Caribbean - Wilson, Lawrence A.
Shortcomings in the Caribbean agricultural institutional system, with particular reference to the training component of the system established since 1948, are identified and an alternative framework and human resources for agricultural training and development are outlined
Keywords: Agricultural education